1996
DOI: 10.1046/j.1365-3059.1996.d01-5.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioassays of glucosinolate‐derived isothiocyanates against postharvest pear pathogens

Abstract: The present study assayed the effect of six isothiocyanates (ITCs), produced by the enzymatic hydrolysis of glucosinolates, on fungal pathogens of pear. Sample pear fruits were artificially inoculated through induced wounds with conidial suspensions of Botrytis cinereaRhizopus stoloniferMonilinia laxaMucor piriformis or Penicillium expansum and were then treated with ITCs. Of the six ITCs tested, the ITC from glucoraphenin showed the highest effectiveness after 6 days at 20°C, against M. laxaB. cinerea and M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 22 publications
1
37
0
3
Order By: Relevance
“…The differences in fungicidal activity of BITC observed in vitro and in vivo are consistent with other reports. 27,41 The low effectiveness of BITC applied in vivo compared with in vitro could be related to the more complex composition of the ripe fruit as compared with the PDA used during the in vitro test, and the possible escape of the volatile compound through the lowdensity polyethylene film used in the experiment.…”
Section: In Vitro Antifungal Activity Of Bitc On a Alternatamentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in fungicidal activity of BITC observed in vitro and in vivo are consistent with other reports. 27,41 The low effectiveness of BITC applied in vivo compared with in vitro could be related to the more complex composition of the ripe fruit as compared with the PDA used during the in vitro test, and the possible escape of the volatile compound through the lowdensity polyethylene film used in the experiment.…”
Section: In Vitro Antifungal Activity Of Bitc On a Alternatamentioning
confidence: 99%
“…Most of the studies found in the literature regarding the antifungal activity of BITC refer to in vitro studies, whilst there appears to be a lack of studies dealing with in vivo activity. To the best of our knowledge, the most complete in vivo study of the ITC effect on fungal pathogens was done in pear fruit by Mari et al 27 They found that 4-methylsulfinyl-3-butenyl and p-hydroxyl-benzyl ITC showed consistent antifungal activity against Monilinia laxa and Botrytis cinerea. Furthermore, BITC showed little activity against these pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds and their breakdown products, for example, isothiocyanates, protect plants against herbivores and pathogens (Giamoustaris and Mithen, 1995;Mari et al, 1996;Manici et al, 2000;Reymond et al, 2004;Chung et al, 2005;Mewis et al, 2005;Brader et al, 2006) and are known to serve as human anticancer agents (Talalay and Fahey, 2001;Traw et al, 2003;Hayes et al, 2008). After Met-derived glucosinoates, indolic and benzyl glucosinolates are the most abundant glucosinolates in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…El cual se basó en la metodología establecida por Jezeck et al (1999) para determinar glucosinolatos, mediante espectrofotometría, usando una alcalina degradación y reacción con ferricianuro, utilizando sinigrina como modelo de glucosinolatos, así mismo Gallaher et al (2012) Mari et al (1996) reported that isothiocyanates derived from glucosinolates used at a concentration of 3.6 mµg mL -1 completely controlled the fungus Penicillium expansum in pear fruit. Masahiro et al, (2006) tested concentrations of 20 mg g -1 of volatile compounds of Brasicca rapa, inhibited the mycelial growth of Rhizoctonia solani.…”
Section: Resultados Y Discusión Determinación Espectrofotométrica De unclassified
“…Varios autores han demostrado previamente que los GLs tienen efecto en contra de algunos patógenos. Mari et al (1996) reportan que los isotiocinatos derivados de los glucosinolatos usados a una concentración de 3.6 mg mL -1 controlaron completamente al hongo Penicillium expansum en frutos de pera. Masahiro et al (2006), probaron concentraciones de 20 mg g -1 de compuestos volátiles de Brasicca rapa inhibió el crecimiento micelial de Rhizoctonia solani.…”
Section: Actividad Del Jugo De Brócoli (Gls) In Vitro En Alternaria Aunclassified